2020
DOI: 10.1016/j.jaci.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Regulating metabolic inflammation by nutritional modulation

Abstract: Metabolic inflammation (metaflammation) is characteristic of obesity-related metabolic disorders, associated with increased risk of development of type 2 diabetes, nonalcoholic fatty liver disease (NAFLD), or cardiovascular disease. Metaflammation refers to a chronic, low-grade systemic inflammation as opposed to the classical transient and acute inflammatory responses of the innate immune system. Metaflammation is driven by a range of adverse dietary factors, including saturated fatty acids and some sugars, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 193 publications
(228 reference statements)
0
33
0
Order By: Relevance
“…We have previously found that mice fed Western Diet (WD) showed increased disease severity and mortality in a model of endotoxemia, independent of the WD-dependent microbiome or associated weight gain (1). Considering the WD is enriched in dietary saturated fatty acids (SFAs), which have been shown to enhance production of inflammatory cytokines from innate immune cells in vitro (14)(15)(16)(17). Thus, we sought to understand if enriched dietary SFAs were sufficient to drive enhanced endotoxemia severity and mortality in vivo.…”
Section: Diets Enriched In Saturated Fatty Acids Increase Endotoxemia Severity and Mortalitymentioning
confidence: 99%
“…We have previously found that mice fed Western Diet (WD) showed increased disease severity and mortality in a model of endotoxemia, independent of the WD-dependent microbiome or associated weight gain (1). Considering the WD is enriched in dietary saturated fatty acids (SFAs), which have been shown to enhance production of inflammatory cytokines from innate immune cells in vitro (14)(15)(16)(17). Thus, we sought to understand if enriched dietary SFAs were sufficient to drive enhanced endotoxemia severity and mortality in vivo.…”
Section: Diets Enriched In Saturated Fatty Acids Increase Endotoxemia Severity and Mortalitymentioning
confidence: 99%
“…Finally, the regulation of metabolic inflammation using novel therapeutic tools, such as modification of gut microbiota and nutritional modulation, is expected to have a role in the future management of T2D and obesity. 133…”
Section: Future Directionsmentioning
confidence: 99%
“…int/news-room/fact-sheets/detail/obesity-and-overweight). Driven by easy access to energy-dense foods and a sedentary lifestyle, obesity has become a major global health and socio-economic problem in the twenty-first century (1), leading to insulin resistance (IR), a pro-inflammatory and hypoxic milieu, and type 2 diabetes (T2D) (2). More recently there has also been concern that the prevalence of obesity-related cancers will rise.…”
Section: Personalized Nutritionmentioning
confidence: 99%
“…While dietary guidelines are evidence-based and valuable for the general population to maintain health, it has become increasingly clear that it may be important to personalize dietary advice to obtain more effective prevention and treatment of chronic metabolic diseases. Indeed, lifestyle intervention, focused on personalization of general guidelines for a healthy diet and physical activity at an individual level, may reduce diabetes and metabolic syndrome risk by more than 50% in different settings worldwide (2)(3)(4). Nevertheless, within these tailored interventions, 30% of the participants do not respond and/or adhere to the intervention.…”
Section: Personalized Nutritionmentioning
confidence: 99%